Slurry and grinding method

By using slurries with specific cerium oxide particle content and particle size, the insulating material in semiconductor component manufacturing is ground, and the problem of eliminating high-step difference in 3D-NAND devices is solved, and efficient grinding speed and maintenance rate are achieved.

CN119895540APending Publication Date: 2025-04-25RESONAC CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380037519.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-25
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In semiconductor component manufacturing, the step difference of the insulation material of 3D-NAND devices is high, which leads to the need to quickly eliminate high step difference and increase the grinding speed in the CMP process. It is difficult for the prior art to effectively solve this problem.

Method used

A grinding liquid with a slurry containing cerium oxide particles is used, and the specific peak line width ratio in the X-ray diffraction pattern of the cerium oxide particles is 2.50-3.30, an average particle diameter is 200-400 nm, a content of 0.01-10.00 mass %, and a pH of 1.00-7.00 is used to grind the insulating material.

Benefits of technology

The high grinding speed of the insulating material is achieved, and the grinding speed decreases with time is suppressed, and the maintenance rate of the grinding speed is improved, so that the high-step difference can be quickly eliminated in the CMP process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119895540A_ABST
    Figure CN119895540A_ABST
Patent Text Reader

Abstract

A slurry containing abrasive grains and water, the abrasive grains containing cerium oxide particles, the peak value P of the maximum intensity existing in the range of diffraction angle 2 [theta] = 27.000-29.980 deg in the X-ray diffraction pattern of the cerium oxide particles, and the peak value P of the maximum intensity existing in the range of diffraction angle 2 [theta] = 27.000-29.980 deg. The ratio (Wa / Wb) of the peak line width (Wa) at 10% of the maximum strength and the peak line width (Wb) at 50% of the maximum strength is 2.50-3.30.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a slurry, a grinding method and the like. Background Art

[0002] In the manufacturing process of semiconductor devices in recent years, the importance of processing technology for high density and miniaturization has become increasingly high. CMP (Chemical Mechanical Polishing) technology, one of the processing technologies, has become a necessary technology in the manufacturing process of semiconductor devices for the formation of shallow trench isolation (hereinafter referred to as "STI"), the flattening of pre-metal insulating materials or interlayer insulating materials, the formation of plugs or embedded metal wiring, etc.

[0003] As the most commonly used polishing liquid, for example, there can be mentioned a silica polishing liquid containing silica (silicon oxide) particles such as fumed silica and colloidal silica as abrasive particles. The silica polishing liquid is characterized by high versatility, and by appropriately selecting the abrasive content, pH, additives, etc., it can polish various types of materials regardless of insulating materials or conductive materials.

[0004] On the other hand, the demand for cerium oxide-based polishing fluids containing cerium oxide particles as abrasives is increasing. For example, cerium oxide-based polishing fluids can quickly polish insulating materials even at a lower abrasive content than silicon dioxide-based polishing fluids (for example, refer to the following patent documents 1 and 2).

[0005] Previous technical literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 10-106994

[0008] Patent Document 2: Japanese Patent Application Laid-Open No. 08-022970 Summary of the invention

[0009] Technical issues to be solved by the invention

[0010] In recent years, 3D-NAND devices with vertically stacked cell parts have emerged. In this technology, the step difference of the insulating material when forming the cell becomes several times higher than that of the previous planar type. As a result, in order to maintain the productivity of device manufacturing, it is necessary to quickly eliminate the high step difference as described above in the CMP process, etc., and it is necessary to increase the grinding speed of the insulating material.

[0011] One aspect of the present invention is to provide a slurry capable of achieving a high polishing rate for insulating materials. Another aspect of the present invention is to provide a polishing method using such a slurry.

[0012] Means for solving technical problems

[0013] The present invention relates in some aspects to the following [1] to [7] and the like.

[0014] [1] A slurry comprising abrasive and water, wherein the abrasive comprises cerium oxide particles, wherein in a peak of maximum intensity existing in a range of diffraction angles 2θ=27.000 to 29.980 degrees in an X-ray diffraction spectrum of the cerium oxide particles, a ratio Wa / Wb of a peak line width Wa at an intensity of 10% of the maximum intensity to a peak line width Wb at an intensity of 50% of the maximum intensity is 2.50 to 3.30.

[0015] [2] The slurry according to [1], wherein the ratio Wa / Wb is 2.70 to 3.20.

[0016] [3] The slurry according to [1] or [2], wherein the average particle size of the abrasive grains is 200 to 400 nm.

[0017] [4] The slurry according to any one of [1] to [3], wherein the content of the abrasive grains is 0.01 to 10.00% by mass.

[0018] [5] The slurry according to any one of [1] to [4], wherein the pH thereof is 1.00 to 7.00.

[0019] [6] The slurry according to any one of [1] to [5], which is used for polishing a polishing surface containing silicon oxide.

[0020] [7] A polishing method comprising the step of polishing a surface to be polished using the slurry according to any one of [1] to [6].

[0021] Effects of the Invention

[0022] According to one aspect of the present invention, a slurry capable of achieving a high polishing rate for an insulating material can be provided. According to another aspect of the present invention, a polishing method using such a slurry can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a diagram for explaining a method for obtaining the peak line widths Wa and Wb in an X-ray diffraction spectrum of cerium oxide particles. DETAILED DESCRIPTION

[0024] Hereinafter, embodiments of the present invention will be described in detail.

[0025] <Definition>

[0026] In this specification, the numerical range indicated by "~" indicates a range including the numerical values ​​recorded before and after "~" as the minimum and maximum values, respectively. "Above A" in the numerical range refers to A and the range exceeding A. "Below A" in the numerical range refers to A and the range less than A. In the numerical range described in stages in this specification, the upper limit or lower limit of the numerical range of a certain stage can be arbitrarily combined with the upper limit or lower limit of the numerical range of other stages. In the numerical range described in this specification, the upper limit or lower limit of the numerical range can be replaced by the value shown in the embodiment. "A or B" can include either A and B, or both. Unless otherwise specified, the materials exemplified in this specification can be used alone or in combination of two or more. Regarding the content of each component in the composition, when there are multiple substances corresponding to each component in the composition, unless otherwise specified, it refers to the total amount of the multiple substances present in the composition. Regarding the term "film", in addition to the structure of the shape formed on the entire surface when observed in a top view, it also includes the structure of the shape formed in a part. The term "process" does not only include independent processes, but also includes processes that cannot be clearly distinguished from other processes as long as the intended effect of the process is achieved.

[0027] As described later, the slurry involved in this embodiment contains abrasive grains. Abrasive grains are also called "abrasive particles", but are referred to as "abrasive grains" in this specification. Abrasive grains are generally solid particles, and when grinding, the mechanical action of the abrasive grains and the chemical action of the abrasive grains (mainly the surface of the abrasive grains) remove the object to be removed, but it is not limited to this.

[0028] <Slurry>

[0029] The slurry involved in this embodiment contains abrasive grains and water. The slurry involved in this embodiment can be used as a polishing liquid (CMP polishing liquid), for example. In this specification, "polishing liquid" is defined as a composition that contacts the polished surface during polishing. The term "polishing liquid" itself does not limit any component contained in the polishing liquid.

[0030] In the slurry involved in this embodiment, the abrasive contains cerium oxide particles, and in the peak P of maximum intensity existing in the range of diffraction angle 2θ=27.000~29.980deg in the X-ray diffraction spectrum of the cerium oxide particles, the ratio Wa / Wb (hereinafter referred to as "parameter X". X=Wa / Wb) of the peak line width Wa at an intensity of 10% of the maximum intensity and the peak line width Wb at an intensity of 50% of the maximum intensity is 2.50~3.30.

[0031] According to the slurry involved in this embodiment, a high polishing rate of an insulating material can be obtained, for example, a high polishing rate of silicon oxide can be obtained. According to the slurry involved in this embodiment, in the evaluation method described in the examples described later, as a polishing rate for 20 seconds polishing, for example, 1700nm / min or more (preferably 1750nm / min or more, 1800nm / min or more, 1900nm / min or more, 2000nm / min or more, etc.) can be obtained.

[0032] When a slurry is used as a cerium oxide polishing liquid to quickly eliminate the high step difference of an insulating material (such as silicon oxide), its polishing speed decreases as the polishing proceeds. As a result, the phenomenon that the time required to eliminate the step difference becomes longer becomes a problem. Therefore, for the slurry used to eliminate the high step difference, both the initial high polishing speed and the maintenance of the polishing speed are required. According to one mode of the slurry involved in this embodiment, a high polishing speed of the insulating material can be obtained, and the polishing speed decreases as the polishing proceeds. For example, a high polishing speed of silicon oxide can be obtained, and the polishing speed decreases as the polishing proceeds. According to one mode of the slurry involved in this embodiment, in the evaluation method described in the examples described later, as the maintenance rate of the polishing speed (polishing speed for 50 seconds of polishing / polishing speed for 20 seconds of polishing), for example, more than 75.0% (preferably more than 75.3%, more than 80.0%, more than 85.0%, more than 88.0%, more than 90.0%, more than 95.0%, more than 98.0%, etc.) can be obtained.

[0033] The main reason why a high polishing rate of the insulating material can be obtained and a decrease in the polishing rate as the polishing progresses is suppressed is not clear, but is presumed to be as follows. However, the main reason is not limited to the following.

[0034] That is, according to the understanding of the inventors, the adjustment of the shape of the peak P of the maximum intensity existing within the range of the specified diffraction angle in the X-ray diffraction spectrum of the cerium oxide particles is effective for adjusting the grinding speed of the insulating material and the maintenance of the grinding speed. By adjusting the parameter X that represents the expansion mode of the base of the peak P, the grinding speed of the insulating material and the maintenance of the grinding speed can be well balanced. It is speculated as follows: the parameter X depends on the state of the fine microcrystalline components in the cerium oxide particles. Particles containing a large amount of fine microcrystalline components and many grain boundaries break at the grain boundaries as the grinding proceeds, thereby easily exposing new crystal faces with high reactivity (high chemical reactivity), but with the small particles, the physical grinding performance sometimes decreases. On the other hand, it is speculated as follows: when the parameter X satisfies the above-mentioned specified range, the state of the fine microcrystalline components is preferred, thereby improving the chemical reactivity of the abrasive without reducing the physical grinding performance, and the grinding speed of the insulating material and the maintenance of the grinding speed can be well balanced.

[0035] According to one mode of the slurry involved in this embodiment, in the evaluation method described in the examples described later, the polishing speed for 50 seconds of polishing can be, for example, 1300 nm / min or more (preferably 1400 nm / min or more, 1500 nm / min or more, 1600 nm / min or more, 1700 nm / min or more, etc.).

[0036] According to the present embodiment, a method for adjusting a polishing speed can be provided, wherein the polishing speed is adjusted according to a parameter X, and a method for adjusting a maintenance rate of a polishing speed can be provided, wherein the maintenance rate of the polishing speed is adjusted according to the parameter X. According to the present embodiment, a method for selecting abrasive grains can be provided, wherein abrasive grains comprising cerium oxide particles are selected according to the parameter X. According to the present embodiment, a slurry can be provided for use in polishing a polished surface comprising an insulating material, and a slurry can be provided for use in polishing a polished surface comprising silicon oxide. According to the present embodiment, a slurry can be provided for use in a flattening process of a substrate surface as a manufacturing technology for semiconductor elements. According to the present embodiment, a slurry can be provided for use in a flattening process of an STI insulating material, a pre-metal insulating material, or an interlayer insulating material.

[0037] (Abrasive particles)

[0038] The slurry according to the present embodiment contains abrasive grains, and the abrasive grains include cerium oxide particles (particles containing cerium oxide). The cerium oxide in the cerium oxide particles may contain tetravalent cerium or trivalent cerium.

[0039] The abrasive grains may include particles different from cerium oxide particles. Examples of particles different from cerium oxide particles include silicon oxide (silicon dioxide) particles, aluminum oxide (alumina) particles, silicon nitride particles, zirconium oxide (zirconia: zirconium oxide particles with yttria added, etc.) particles, titanium oxide (titanium dioxide) particles, yttria (yttria) particles, silicon carbide particles, diamond particles, polymer particles, and the like.

[0040] The content of cerium oxide (cerium oxide particles) may be within the following ranges based on the total mass of the abrasive grains (the total mass of the abrasive grains contained in the slurry). From the viewpoint of easily obtaining a high polishing rate for the insulating material, the content of cerium oxide (cerium oxide particles) may be 20% by mass or more, 30% by mass or more, 40% by mass or more, 50% by mass or more, more than 50% by mass, 60% by mass or more, 70% by mass or more, 80% by mass or more, 90% by mass or more, 95% by mass or more, 98% by mass or more, or 99% by mass or more. The abrasive grains contained in the slurry may be substantially formed of cerium oxide (cerium oxide particles) (a form in which the content of cerium oxide (cerium oxide particles) is substantially 100% by mass based on the total mass of the abrasive grains contained in the slurry).

[0041] Regarding cerium oxide particles, for example, they can be obtained by oxidizing cerium compounds. As a method for oxidizing cerium compounds, a calcination method can be cited; an oxidation method based on hydrogen peroxide, etc., can be a calcination method from the perspective of easily obtaining a high polishing rate for insulating materials and easily suppressing the decrease in polishing rate as polishing proceeds. As cerium compounds, cerium carbonate, cerium nitrate, cerium sulfate, cerium oxalate, etc. can be cited. From the perspective of easily obtaining a high polishing rate for insulating materials and easily suppressing the decrease in polishing rate as polishing proceeds, the cerium compound can be cerium carbonate, and the cerium oxide particles can contain an oxide derived from cerium carbonate.

[0042] Cerium carbonate for obtaining cerium oxide particles can be obtained, for example, by the following steps using natural minerals as raw materials. First, unnecessary gangue is removed from an ore (fluorocarbon cerium ore, heavy sand, iron dolomite, etc.) containing at least a rare earth element containing cerium by ore dressing, thereby obtaining a rare earth concentrate (fluorocarbon cerium concentrate, monazite concentrate, Chinese complex concentrate, etc.). Then, after chemical treatment (alkali decomposition, sulfuric acid decomposition, hydroxide precipitation method, etc.) is applied to the rare earth concentrate to reduce insoluble components such as impurities, rare earth elements (neodymium, etc.) are reduced by solvent extraction as needed, thereby obtaining a cerium-containing rare earth salt solution. Then, by mixing the cerium-containing rare earth salt solution and sodium carbonate, cerium carbonate can be obtained. For convenience, the manufacturing method of this cerium carbonate is defined as "extraction method".

[0043] The sodium carbonate used in the "extraction method" is changed to other salts, thereby other cerium salts (cerium nitrate, cerium sulfate, cerium oxalate, etc.) can be synthesized. For example, by mixing a cerium-containing rare earth salt solution and sodium nitrate, cerium nitrate (for example, cerium (III) nitrate) can be obtained. By reacting an aqueous solution of a cerium salt with a solution of a precursor having a carbonyl group, cerium carbonate can be obtained. For example, by reacting an aqueous solution of cerium nitrate (for example, cerium (III) nitrate) with a solution of a precursor having a carbonyl group at a temperature of 80 to 100° C., cerium carbonate can be precipitated. As a precursor having a carbonyl group, urea and the like can be used. For convenience, the method for manufacturing this cerium carbonate is defined as a "carbonyl substitution method". From the viewpoint of easily obtaining a high polishing speed of an insulating material and easily suppressing the reduction in polishing speed as polishing proceeds, the method for manufacturing cerium carbonate in the present embodiment can be any one of the "extraction method" and the "carbonyl substitution method", or it can be the "carbonyl substitution method".

[0044] In the slurry involved in the present embodiment, in the peak of the maximum intensity existing in the range of diffraction angle 2θ=27.000 to 29.980 degrees (hereinafter referred to as "peak P") in the X-ray diffraction spectrum (XRD pattern) of the cerium oxide particles, the ratio Wa / Wb (parameter X=Wa / Wb) of the peak line width Wa at 10% intensity of the maximum intensity and the peak line width Wb at 50% intensity of the maximum intensity is 2.50 to 3.30. The parameter X can be used as an index representing the expansion mode of the base of the main peak P appearing in the range of 2θ=27.000 to 29.980 degrees in the X-ray diffraction spectrum of the cerium oxide particles. In the present embodiment, the base of the peak P has a specific expansion mode. In the peak P, the peak line width at 10% intensity of the maximum intensity is used instead of the peak line width at zero intensity (no count), thereby avoiding the influence of the background and making it easy to evaluate the expansion mode of the base of the peak P. The peak line width can be called peak width, diffraction line width, etc. The diffraction angle 2θ providing the maximum intensity of the peak P is within the range of 27.000 to 29.980 degrees.

[0045] When the maximum intensity of the peak P (highest count number, peak apex) is set to 100%, and the intensity zero (no count) in the X-ray diffraction pattern is set to 0%, as shown in FIG. Figure 1As shown, the peak line width Wa is the peak line width [deg] at an intensity (number of counts) equivalent to 10% of the maximum intensity, and the peak line width Wb is the peak line width [deg] at an intensity (number of counts) equivalent to 50% of the maximum intensity. When measuring the peak line widths Wa and Wb from the X-ray diffraction pattern, when the background is large relative to the peak P, the background can be removed by a general background removal method (Sonneveld-Visser method, etc.). The X-ray diffraction pattern used to calculate the parameter X can be obtained using a general powder X-ray diffraction device, for example, as an XRD using CuKα rays, it can be obtained by the method described in the examples described later.

[0046] It is speculated that when the parameter X is 2.50 or more, the chemical reactivity of the cerium oxide particles is increased, and the polishing rate of the insulating material is increased. It is speculated that when the parameter X is 3.30 or less, the physical strength of the cerium oxide particles is increased, and the polishing rate of the insulating material and the maintenance of the polishing rate are increased.

[0047] From the viewpoint of easily improving the chemical reactivity of cerium oxide particles and easily improving the polishing speed and the maintenance of the polishing speed of insulating materials, the parameter X may be 2.55 or more, 2.60 or more, 2.63 or more, 2.64 or more, 2.65 or more, 2.70 or more, more than 2.70, 2.71 or more, 2.72 or more, or 2.73 or more. From the viewpoint of easily improving the polishing speed of insulating materials, the parameter X may be 2.75 or more, 2.80 or more, 2.85 or more, 2.90 or more, 2.95 or more, or 2.97 or more. From the viewpoint of easily improving the physical strength of cerium oxide particles and easily improving the polishing speed and the maintenance of the polishing speed of insulating materials, the parameter X may be 3.20 or less, less than 3.20, 3.15 or less, 3.10 or less, less than 3.10, 3.05 or less, 3.00 or less, less than 3.00, or 2.98 or less. From the viewpoint of easily improving the maintainability of the polishing rate, the parameter X may be 2.97 or less, 2.95 or less, 2.90 or less, 2.85 or less, 2.80 or less, 2.75 or less, or 2.73 or less. The parameter X may be 2.72 or less, 2.71 or less, 2.70 or less, 2.65 or less, 2.64 or less, or 2.63 or less. From these viewpoints, the parameter X may be 2.60 to 3.30, 2.70 to 3.30, 2.80 to 3.30, 2.90 to 3.30, 2.50 to 3.20, 2.60 to 3.20, 2.70 to 3.20, 2.80 to 3.20, 2.90 to 3.20, 2.50 to 3.00, 2.60 to 3.00, 2.7 0~3.00, 2.80~3.00, 2.90~3.00, 2.50~2.97, 2.60~2.97, 2.70~2.97, 2.80~2.97, 2.90~2.97, 2.50~2.80, 2.60~2.80, 2.70~2.80, 2.50~2.70 or 2.60~2.70.

[0048] Methods for adjusting the parameter X include: changing the composition of the raw materials; changing the method for preparing the raw materials; changing the firing temperature, firing time, etc. in the firing method; and changing the method and conditions of pulverization, etc. These methods may be used alone or in combination.

[0049] The cerium oxide particles to be measured in the XRD measurement for obtaining the parameter X may be recovered by drying the slurry (drying and solidifying), or may be recovered by separating and removing components other than the cerium oxide particles from the dried product. When the parameter X of the cerium oxide particles does not change when preparing the slurry, the cerium oxide particles to be measured in the XRD measurement may be the cerium oxide particles before being mixed with other components such as water.

[0050] From the viewpoint of obtaining a high polishing rate for the insulating material and easily suppressing a decrease in the polishing rate as the polishing proceeds, the peak line width Wb at 50% of the maximum intensity may be within the following range. The peak line width Wb may be 0.23 deg or more, 0.24 deg or more, 0.25 deg or more, 0.26 deg or more, 0.30 deg or more, 0.31 deg or more, 0.33 deg or more, 0.34 deg or more, 0.35 deg or more, 0.36 deg or more, more than 0.36 deg, 0.40 deg or more, 0.44 deg or more, 0.45 deg or more, 0.50 deg or more, 0.55 deg or more, or 0.60 deg or more. The peak line width Wb can be less than 0.62 degrees, less than 0.60 degrees, less than 0.55 degrees, less than 0.50 degrees, less than 0.45 degrees, less than 0.44 degrees, less than 0.40 degrees, less than 0.36 degrees, less than 0.35 degrees, less than 0.34 degrees, less than 0.33 degrees, less than 0.31 degrees, less than 0.30 degrees, less than 0.26 degrees, less than 0.26 degrees, less than 0.25 degrees or less than 0.24 degrees. From these viewpoints, the peak line width Wb may be 0.23 to 0.62 degrees, 0.23 to 0.45 degrees, 0.23 to 0.40 degrees, 0.23 to 0.33 degrees, 0.25 to 0.62 degrees, 0.25 to 0.45 degrees, 0.25 to 0.40 degrees, 0.25 to 0.33 degrees, 0.33 to 0.62 degrees, 0.33 to 0.45 degrees, 0.33 to 0.40 degrees, 0.40 to 0.62 degrees, 0.40 to 0.45 degrees, or 0.45 to 0.62 degrees.

[0051] The average particle size of the abrasive grains or the average particle size of the cerium oxide particles may be within the following ranges. From the viewpoint of easily obtaining a high polishing rate for the insulating material, the average particle size may be 100 nm or more, 150 nm or more, 175 nm or more, more than 175 nm, 180 nm or more, 200 nm or more, 220 nm or more, 230 nm or more, 240 nm or more, 245 nm or more, 250 nm or more, 255 nm or more, 260 nm or more, 265 nm or more, 270 nm or more, 275 nm or more, or 280 nm or more. From the viewpoint of easily reducing scratches caused by grinding, the average particle size can be 600nm or less, 550nm or less, less than 550nm, 500nm or less, 450nm or less, 400nm or less, 350nm or less, 320nm or less, 300nm or less, 295nm or less, 290nm or less, 285nm or less, 280nm or less, 275nm or less, 270nm or less, 265nm or less, 260nm or less, 255nm or less, or 250nm or less. From these viewpoints, the average particle size may be 100 to 600 nm, 100 to 500 nm, 100 to 400 nm, 100 to 300 nm, 100 to 280 nm, 200 to 600 nm, 200 to 500 nm, 200 to 400 nm, 200 to 300 nm, 200 to 280 nm, 250 to 600 nm, 250 to 500 nm, 250 to 400 nm, 250 to 300 nm, 250 to 280 nm, 270 to 600 nm, 270 to 500 nm, 270 to 400 nm, 270 to 300 nm or 270 to 280 nm.

[0052] The average particle size refers to the value of MV (volume average diameter) measured by a laser diffraction particle size distribution meter, and can be measured, for example, by the method described in the examples described later. The average particle size (volume average diameter) can be measured by diluting the slurry with water to adjust the content of the abrasive or the content of the cerium oxide particles to an appropriate content. For example, in the case of the product name "SYNC" manufactured by MicrotracBEL Corp., the DV (Diffraction Volume) value can be adjusted to a content of 0.0010 to 0.0150. The DV value is a concentration index using the total amount of scattered light from the sample received by the detector. If the content of the abrasive or the content of the cerium oxide particles in the sample increases, there is a tendency to increase. When a slurry containing abrasive (abrasive containing cerium oxide particles), an additive and water is divided into a first liquid containing abrasive and water and a second liquid containing an additive and water and stored, the content of the abrasive can be adjusted to an appropriate content by diluting the first liquid with water, and the average particle size can be measured.

[0053] Examples of methods for adjusting the average particle size include: adjusting the composition of the raw materials, the preparation method, the calcination temperature, the calcination time, etc.; pulverization; classification; and filtration. Pulverization, classification, and filtration may be performed on the abrasive particles or the cerium oxide particles, or may be performed on the raw materials (cerium compounds such as cerium carbonate) used to obtain the cerium oxide particles.

[0054] Based on the total mass of the slurry, the content of the abrasive in the slurry can be within the following range. From the perspective of easily obtaining a high polishing rate for insulating materials, the content of the abrasive can be 0.01 mass %, 0.05 mass %, 0.10 mass %, 0.15 mass %, 0.30 mass %, 0.50 mass %, 0.80 mass %, 1.00 mass %, 1.20 mass %, 1.50 mass %, 1.80 mass %, or 2.00 mass %. From the perspective of suppressing the aggregation of particles and not easily generating scratches on the polished surface, the content of the abrasive can be 20.00 mass %, 15.00 mass %, 10.00 mass %, 8.00 mass %, 5.00 mass %, 4.50 mass %, 4.00 mass %, 3.50 mass %, 3.00 mass %, 2.50 mass % or 2.00 mass %. From these viewpoints, the content of the abrasive grains may be 0.01 to 20.00 mass%, 0.01 to 10.00 mass%, 0.01 to 5.00 mass%, 0.10 to 20.00 mass%, 0.10 to 10.00 mass%, 0.10 to 5.00 mass%, 0.50 to 20.00 mass%, 0.50 to 10.00 mass%, 0.50 to 5.00 mass%, 1.00 to 20.00 mass%, 1.00 to 10.00 mass%, or 1.00 to 5.00 mass%.

[0055] (water)

[0056] The water is not particularly limited, and examples thereof include deionized water, ultrapure water, etc. The content of water may be the remainder of the slurry excluding the contents of other components, and is not particularly limited.

[0057] From the viewpoint of easily obtaining a high polishing rate of an insulating material and easily suppressing the reduction of the polishing rate as the polishing proceeds, the content of water in the slurry can be within the following ranges based on the total mass of the slurry. The content of water can be 50% by mass or more, 70% by mass or more, 80% by mass or more, 90% by mass or more, 93% by mass or more, 95% by mass or more, 96% by mass or more, or 97% by mass or more. The content of water can be less than 100% by mass, 99% by mass or less, or 98% by mass or less. From these viewpoints, the content of water can be 50% by mass or more and less than 100% by mass, 50 to 99% by mass, 50 to 98% by mass, 80% by mass or more and less than 100% by mass, 80% to 99% by mass, 80% to 98% by mass, 90% by mass or more and less than 100% by mass, 90% to 99% by mass, or 90% to 98% by mass.

[0058] (additive)

[0059] The slurry involved in this embodiment may contain any additive or may not contain any additive. As the arbitrary additive, polar solvents (ethanol, acetone, etc.), materials having carboxyl groups (except polyoxyalkylene compounds or compounds corresponding to water-soluble polymers), polyoxyalkylene compounds, water-soluble polymers, oxidants (such as hydrogen peroxide), dispersants (such as phosphoric acid inorganic salts), etc. can be cited.

[0060] Examples of materials having a carboxyl group include monocarboxylic acids such as acetic acid, propionic acid, butyric acid, and valeric acid; hydroxy acids such as lactic acid, malic acid, and citric acid; dicarboxylic acids such as malonic acid, succinic acid, fumaric acid, and maleic acid; and amino acids such as arginine, histidine, and lysine.

[0061] Examples of the polyoxyalkylene compound include polyalkylene glycols and polyoxyalkylene derivatives.

[0062] Examples of the polyalkylene glycol include polyethylene glycol, polypropylene glycol, and polybutylene glycol.

[0063] The polyoxyalkylene derivative is, for example, a compound in which a functional group or a substituent is introduced into a polyalkylene glycol or a compound in which a polyalkylene oxide is added to an organic compound. Examples of the functional group or the substituent include an alkyl ether group, an alkylphenyl ether group, a phenyl ether group, a styrenated phenyl ether group, a glycerol ether group, an alkylamine group, a fatty acid ester group, and an ethylene glycol ester group. Examples of the polyoxyalkylene derivatives include polyoxyethylene alkyl ethers, polyoxyethylene bisphenol ethers (e.g., BA Glycol series manufactured by Nippon Nyukazai Co., Ltd.), polyoxyethylene styrenated phenyl ethers (e.g., EMULGEN series manufactured by Kao Corporation), polyoxyethylene alkyl phenyl ethers (e.g., NOIGEN EA series manufactured by DKS Co., Ltd.), polyoxyalkylene polyglycerol ethers (e.g., SC-E series and SC-P series manufactured by Sakamoto Yakuhin Kogyo Co., Ltd.), polyoxyethylene sorbitan fatty acid esters (e.g., SOLGEN TW series manufactured by DKS Co., Ltd.), polyoxyethylene fatty acid esters (e.g., EMANONE series manufactured by Kao Corporation), polyoxyethylene alkylamines (e.g., AMILADIN D manufactured by DKS Co., Ltd.), and other compounds to which polyalkylene oxides are added (e.g., SURFYNOL 465 manufactured by Nissin Chemical Industry Co., Ltd.; Nippon Nyukazai Co., Ltd., TMP series) etc.

[0064] The water-soluble polymer has the effect of adjusting the dispersion stability of the abrasive grains, etc. "Water-soluble polymer" is defined as a polymer that dissolves 0.1 g or more in 100 g of water. The polymer corresponding to the polyoxyalkylene compound is not included in the "water-soluble polymer".

[0065] Examples of water-soluble polymers include polycarboxylic acids such as polyacrylic acid and polymaleic acid; acrylic polymers such as polyacrylamide and polydimethylacrylamide; polysaccharides such as carboxymethyl cellulose, agar, thermogel, dextrin, cyclodextrin, and pullulan; vinyl polymers such as polyvinyl alcohol, polyvinyl pyrrolidone, and polyacrolein; glycerol polymers such as polyglycerol and polyglycerol derivatives, etc.

[0066] From the viewpoint of suppressing the precipitation of abrasive grains and easily obtaining the effect of adding the water-soluble polymer, the content of the water-soluble polymer may be within the following range based on the total mass of the slurry. The content of the water-soluble polymer may be 0.001 mass % or more, 0.005 mass % or more, 0.010 mass % or more, 0.020 mass % or more, 0.030 mass % or more, 0.040 mass % or more, 0.050 mass % or more, 0.060 mass % or more, 0.070 mass % or more, or 0.075 mass % or more. The content of the water-soluble polymer may be 10.000 mass % or less, 8.000 mass % or less, 6.000 mass % or less, 5.000 mass % or less, 3.000 mass % or less, 1.000 mass % or less, 0.500 mass % or less, 0.300 mass % or less, 0.100 mass % or less, 0.080 mass % or less, or 0.075 mass % or less. From these viewpoints, the content of the water-soluble polymer may be 0.001 to 10.000 mass%, 0.001 to 1.000 mass%, 0.001 to 0.500 mass%, 0.001 to 0.100 mass%, 0.010 to 10.000 mass%, 0.010 to 1.000 mass%, 0.010 to 0.500 mass%, 0.010 to 0.100 mass%, 0.030 to 10.000 mass%, 0.030 to 1.000 mass%, 0.030 to 0.500 mass%, 0.030 to 0.100 mass%, 0.050 to 10.000 mass%, 0.050 to 1.000 mass%, 0.050 to 0.500 mass%, or 0.050 to 0.100 mass%.

[0067] (pH)

[0068] The pH of the slurry according to the present embodiment may be within the following ranges. From the viewpoint of easily obtaining a high polishing rate for the insulating material, the pH may be 1.00 or more, 1.50 or more, 2.00 or more, 2.50 or more, 3.00 or more, more than 3.00, 3.50 or more, more than 3.50, 4.00 or more, more than 4.00, 4.10 or more, 4.20 or more, 4.30 or more, 4.40 or more, 4.50 or more, more than 4.50, 4.60 or more, 4.70 or more, or 4.80 or more. From the viewpoint of easily improving the storage stability of the slurry, the pH may be 7.00 or less, less than 7.00, 6.50 or less, less than 6.50, 6.00 or less, less than 6.00, 5.50 or less, less than 5.50, 5.00 or less, less than 5.00, 4.90 or less, 4.85 or less, 4.80 or less, 4.75 or less, 4.70 or less, 4.65 or less, 4.60 or less, 4.55 or less, 4.50 or less, less than 4.50, 4.45 or less, 4.40 or less, 4.35 or less, 4.30 or less, 4.25 or less, or 4.20 or less. From these viewpoints, the pH may be 1.00 to 7.00, 1.00 to 6.00, 1.00 to 5.00, 1.00 to 4.50, 2.00 to 7.00, 2.00 to 6.00, 2.00 to 5.00, 2.00 to 4.50, 3.00 to 7.00, 3.00 to 6.00, 3.00 to 5.00, 3.00 to 4.50, 4.00 to 7.00, 4.00 to 6.00, 4.00 to 5.00, or 4.00 to 4.50. The pH of the slurry is defined as the pH at a liquid temperature of 25°C.

[0069] The pH of the slurry can be adjusted by an acid component such as an inorganic acid or an organic acid; an alkali component such as ammonia, sodium hydroxide, tetramethylammonium hydroxide (TMAH), imidazole, or an alkanolamine. In order to stabilize the pH, a buffer may be added, or a buffer solution (a liquid containing a buffer solution) may be added. Examples of the buffer solution include acetate buffer solution and phthalate buffer solution.

[0070] The pH of the slurry involved in this embodiment can be measured using a pH meter (e.g., model PHL-40 manufactured by DKK-TOA CORPORATION). For example, a phthalate pH buffer solution (pH: 4.01) and a neutral phosphate pH buffer solution (pH: 6.86) can be used as standard buffer solutions and the pH meter can be calibrated at two points. Then, the electrode of the pH meter can be placed in the slurry, and the value after stabilization for more than 2 minutes can be measured as the pH of the slurry. The liquid temperature of the standard buffer solution and the slurry is set to 25°C.

[0071] (Save form)

[0072] In the case where the slurry involved in the present embodiment contains any of the above-mentioned additives, the slurry involved in the present embodiment can be stored in a single liquid state containing abrasive grains, additives and water, or can be stored as a multi-liquid (e.g., two-liquid) set in which the constituent components of the slurry are divided into a first liquid and a second liquid in a manner of mixing a first liquid containing abrasive grains and water and a second liquid containing additives and water to form a slurry. The slurry involved in the present embodiment can be a single liquid state containing abrasive grains, additives and water, or can be the first liquid in a multi-liquid set. The second liquid can contain at least one additive, and the first liquid can contain an additive of the same type or a different type as the additive of the second liquid. The constituent components of the slurry can be divided into three or more liquids and stored.

[0073] In the above-mentioned multi-liquid set, the first liquid and the second liquid are mixed to prepare a slurry just before or during grinding. The one-liquid slurry can be stored as a storage liquid with a reduced water content, and diluted with water for use during grinding. The multi-liquid set can store the first liquid and the second liquid as a storage liquid with a reduced water content, and dilute with water for use during grinding.

[0074] <Grinding method>

[0075] The polishing method (substrate polishing method, etc.) of this embodiment includes a polishing step of polishing a polished surface (substrate polishing surface, etc.) using the slurry of this embodiment. The slurry in the polishing step can be a slurry obtained by mixing the first liquid and the second liquid in the multi-liquid set.

[0076] In the grinding process, for example, the insulating material having a substrate of insulating material can be pressed against a grinding pad (grinding cloth) of a grinding platform, and the slurry involved in this embodiment can be supplied between the material to be ground and the grinding pad, and the substrate and the grinding platform can be relatively moved to grind the grinding surface of the insulating material. In the grinding process, for example, at least a portion of the insulating material is removed by grinding.

[0077] As the grinding object, i.e., the base body, a substrate to be ground, etc. can be cited. As the substrate to be ground, for example, a base on which an insulating material is formed on a substrate involved in the manufacture of semiconductor elements (for example, a semiconductor substrate on which an STI pattern, a gate pattern, a wiring pattern, etc. are formed) can be cited. As the insulating material, silicon oxide, etc. can be cited. The insulating material can be a single material or a plurality of materials. In the case where a plurality of materials are exposed on the grinding surface, these can be regarded as insulating materials. The insulating material can be in the form of a film (insulating film) or a silicon oxide film.

[0078] By polishing the insulating material (eg, silicon oxide) formed on the substrate using the slurry according to the present embodiment to remove the excess portion, the surface irregularities of the insulating material are eliminated, and a smooth surface can be obtained over the entire surface of the insulating material.

[0079] In the polishing method of this embodiment, a general polishing device having a support capable of holding a substrate having a polished surface and a polishing platform capable of attaching a polishing pad can be used as a polishing device. A motor capable of changing the rotation speed can be installed on the support and the polishing platform, respectively.

[0080] As grinding pad, general nonwoven fabrics, foam, non-foam etc. can be used. As the material of grinding pad, resins such as polyurethane, acrylic resin, polyester, acrylate copolymer, polytetrafluoroethylene, polypropylene, polyethylene, poly-4-methylpentene, cellulose, cellulose ester, polyamide (for example, nylon (trade name) and aramid), polyimide, polyimide amide, polysiloxane copolymer, ethylene oxide compound, phenolic resin, polystyrene, polycarbonate, epoxy resin can be used. From the viewpoint of easily obtaining excellent grinding speed and flatness, the material of grinding pad can be at least one selected from the group consisting of foamed polyurethane and non-foamed polyurethane. The grinding pad can be implemented as the groove processing of the accumulation slurry.

[0081] There is no limit on the grinding conditions, but in order to prevent the substrate from flying out, the upper limit of the grinding platform speed can be 200min -1 (min -1 = rpm), from the viewpoint of easily suppressing the generation of grinding scratches, the upper limit of the grinding pressure (processing load) applied to the substrate can be 100 kPa or less. During the grinding, the slurry can be continuously supplied to the grinding pad with a pump or the like. The supply amount of the slurry in this case is not limited, but the surface of the grinding pad can always be covered with slurry.

[0082] The slurry and the polishing method of this embodiment can be used to polish the polished surface containing silicon oxide. The slurry and the polishing method of this embodiment can be preferably used for the formation of STI and the high-speed polishing of interlayer insulating materials. In this silicon oxide, part of the constituent elements can be replaced by carbon atoms, nitrogen atoms, etc.

[0083] The slurry and polishing method according to the present embodiment can also be used for polishing pre-metal insulating materials. Examples of pre-metal insulating materials include silicon oxide, phosphorus-silicate glass, boron-phosphorus-silicate glass, silicon oxyfluoride, and fluorinated amorphous carbon.

[0084] The slurry and polishing method of this embodiment can also be applied to materials other than insulating materials such as silicon oxide. Examples of such materials include high dielectric constant materials such as Hf-based, Ti-based, and Ta-based oxides; semiconductor materials such as silicon, amorphous silicon, SiC, SiGe, Ge, GaN, GaP, GaAs, and organic semiconductors; phase change materials such as GeSbTe; inorganic conductive materials such as ITO; polymer resin materials such as polyimide, polybenzoxazole, acrylic, epoxy, and phenol.

[0085] The slurry and polishing method involved in this embodiment can be applied not only to film-shaped polishing objects, but also to various substrates composed of glass, silicon, SiC, SiGe, Ge, GaN, GaP, GaAs, sapphire, plastic, etc.

[0086] The slurry and polishing method involved in this embodiment can be used not only in the manufacture of semiconductor elements, but also in the manufacture of image display devices such as TFT, organic EL; optical parts such as photomasks, lenses, prisms, optical fibers, single crystal scintillators; optical elements such as optical switch elements, optical waveguides; light-emitting elements such as solid lasers, blue laser LEDs; and magnetic storage devices such as disks and magnetic heads.

[0087] <Manufacturing method, etc.>

[0088] The manufacturing method of the part involved in the present embodiment includes a part manufacturing process of obtaining a part using a substrate (grinded part) ground by the grinding method involved in the present embodiment. The part involved in the present embodiment is a part obtained by the manufacturing method of the part involved in the present embodiment. The part involved in the present embodiment is not particularly limited, but can be an electronic part (such as a semiconductor part such as a semiconductor package), a wafer (such as a semiconductor wafer), or a chip (such as a semiconductor chip). As one mode of the manufacturing method of the part involved in the present embodiment, in the manufacturing method of the electronic part of the present embodiment, an electronic part is obtained using a substrate ground by the grinding method involved in the present embodiment. As one mode of the manufacturing method of the part involved in the present embodiment, in the manufacturing method of the semiconductor part of the present embodiment, a semiconductor part (such as a semiconductor package) is obtained using a substrate ground by the grinding method involved in the present embodiment. The manufacturing method of the part involved in the present embodiment may include a grinding process of grinding the substrate by the grinding method involved in the present embodiment before the part manufacturing process.

[0089] The manufacturing method of the part involved in the present embodiment may include a singulation process of singulating the substrate (the part to be polished) polished by the polishing method involved in the present embodiment as a mode of the part manufacturing process. The singulation process may be, for example, a process of cutting a wafer (such as a semiconductor wafer) polished by the polishing method involved in the present embodiment to obtain a chip (such as a semiconductor chip). As a mode of the manufacturing method of the part involved in the present embodiment, the manufacturing method of the electronic part involved in the present embodiment may include a process of singulating the substrate polished by the polishing method involved in the present embodiment to obtain an electronic part (such as a semiconductor part). As a mode of the manufacturing method of the part involved in the present embodiment, the manufacturing method of the semiconductor part involved in the present embodiment may include a process of singulating the substrate polished by the polishing method involved in the present embodiment to obtain a semiconductor part (such as a semiconductor package).

[0090] The manufacturing method of the part involved in the present embodiment, as a mode of the part manufacturing process, may include a connection process of connecting (e.g., electrically connecting) the substrate (grinded part) ground by the grinding method involved in the present embodiment to other connected bodies. The connected body connected to the substrate ground by the grinding method involved in the present embodiment is not particularly limited, and may be the substrate ground by the grinding method involved in the present embodiment, or may be a connected body different from the substrate ground by the grinding method involved in the present embodiment. In the connection process, the substrate and the connected body may be directly connected (connected in a state where the substrate and the connected body are in contact), or the substrate and the connected body may be connected via other components (conductive components, etc.). The connection process can be performed before the singulation process, after the singulation process, or before and after the singulation process.

[0091] The connection process may be a process of connecting the ground surface of the substrate ground by the grinding method involved in the present embodiment to the connected body, or may be a process of connecting the connecting surface of the substrate ground by the grinding method involved in the present embodiment to the connecting surface of the connected body. The connecting surface of the substrate may be the ground surface ground by the grinding method involved in the present embodiment. A connected body having a substrate and a connected body can be obtained by the connection process. In the connection process, when the connecting surface of the substrate has a metal part, the connected body can be brought into contact with the metal part. In the connection process, when the connecting surface of the substrate has a metal part and the connecting surface of the connected body has a metal part, the metal parts can be brought into contact with each other. The metal part may contain copper.

[0092] The device according to the present embodiment (for example, an electronic device such as a semiconductor device) includes at least one selected from the group consisting of a base body polished by the polishing method according to the present embodiment and the component according to the present embodiment.

[0093] Example

[0094] Hereinafter, the present invention will be specifically described based on examples, but the present invention is not limited to the following examples.

[0095] <Preparation of slurry>

[0096] (Comparative Example 1)

[0097] According to the above-mentioned "extraction method", a 0.1 mol / L aqueous solution of cerium (III) sulfate and a 0.1 mol / L aqueous solution of sodium carbonate were maintained at 95°C and mixed at a volume ratio of 1:2, thereby generating a precipitate of cerium carbonate. The precipitate was filtered out and dried to solidify, and a cerium carbonate powder (raw material) was obtained. The cerium carbonate powder was placed in an alumina container, and an oven "HPM-2N" made by AS ONE Corporation was used to calcine the cerium carbonate powder at a calcination temperature of 800°C and in the atmosphere for 1 hour, thereby obtaining a white powder. The phase identification of the powder by XRD confirmed that it was a cerium oxide powder.

[0098] The cerium oxide powder was crushed in a mortar and passed through a sieve with a mesh size of 450 μm to obtain a crushed product. The crushed product, pure water and acetic acid were mixed at a mass ratio of 20.00:79.94:0.06 to obtain a mixture, and the mixture was crushed for 30 minutes using a wet micronizer "STARBURST LABO HJP-25005" (pressure 245 MPa) manufactured by SUGINO MACHINE LIMITED CO., LTD. to obtain a dispersion. The dispersion was centrifuged for 60 seconds using a centrifuge "himac CR7" (rotation speed 2000 rpm) manufactured by Hitachi Koki Co., Ltd., and a dispersion containing cerium oxide particles was obtained as a liquid retained in the upper part of the container after centrifugation. Thereafter, cerium oxide particles were recovered from the dispersion.

[0099] The cerium oxide particles (abrasive grains), pure water, and polyglycerol (manufactured by Sakamoto Yakuhin Kogyo Co., Ltd., product name: polyglycerol #750) were mixed at a mass ratio of 2.000:97.925:0.075 to obtain a polishing slurry.

[0100] (Example 1)

[0101] A polishing slurry was obtained in the same manner as in Comparative Example 1 except that the calcination temperature was changed to 700°C.

[0102] (Example 2)

[0103] According to the above-mentioned "carbonyl substitution method", a 0.1 mol / L aqueous solution of cerium (III) nitrate and a 7.8 mol / L aqueous solution of urea were maintained at 95°C and mixed at a volume ratio of 6:1, thereby generating a precipitate of cerium carbonate. The precipitate was filtered out and dried to solidify, and a cerium carbonate powder (raw material) was obtained. The cerium carbonate powder was placed in an alumina container, and an oven "HPM-2N" made by AS ONE Corporation was used to calcine the cerium carbonate powder at a calcination temperature of 800°C and in the atmosphere for 1 hour, thereby obtaining a white powder. The phase identification of the powder by XRD confirmed that it was a cerium oxide powder.

[0104] The cerium oxide powder was crushed with a mortar and passed through a sieve with a mesh size of 450 μm to obtain a crushed product. The crushed product, pure water and acetic acid were mixed at a mass ratio of 20.00:79.94:0.06 to obtain a mixture, and the mixture was crushed for 10 minutes using a wet micronizer "STARBURST LABO HJP-25005" (pressure 245 MPa) manufactured by SUGINO MACHINE LIMITED CO., LTD. to obtain a dispersion. The dispersion was centrifuged for 60 seconds using a centrifuge "himac CR7" (rotation speed 2000 rpm) manufactured by Hitachi Koki Co., Ltd., and a dispersion containing cerium oxide particles was obtained as a liquid retained in the upper part of the container after centrifugation. Thereafter, cerium oxide particles were recovered from the dispersion.

[0105] The cerium oxide particles (abrasive grains), pure water, and polyglycerol (manufactured by Sakamoto Yakuhin Kogyo Co., Ltd., product name: polyglycerol #750) were mixed at a mass ratio of 2.000:97.925:0.075 to obtain a polishing slurry.

[0106] (Example 3)

[0107] A polishing slurry was obtained in the same manner as in Example 2 except that the calcination temperature was changed to 700°C.

[0108] (Example 4)

[0109] A polishing slurry was obtained in the same manner as in Example 2 except that the calcination temperature was changed to 500°C.

[0110] (Example 5)

[0111] A polishing slurry was obtained in the same manner as in Comparative Example 1 except that the calcination temperature was changed to 600°C.

[0112] (Comparative Example 2)

[0113] A polishing slurry was obtained in the same manner as in Comparative Example 1 except that the calcination temperature was changed to 500°C.

[0114] <Average particle size>

[0115] An appropriate amount of each slurry was placed in a laser diffraction particle size distribution analyzer (manufactured by MicrotracBEL Corp., product name "SYNC", particle refractive index: 2.20) to obtain MV (volume mean diameter) as the average particle size of the abrasive grains. The measurement results are shown in Table 1.

[0116] <Parameter X>

[0117] After placing each of the above slurries in a commercially available evaporating dish, dry and solidify them in a vacuum dryer (manufactured by Yamato Scientific Co., Ltd., ADP200, 40°C, about 1000 Pa) for 24 hours to obtain a dried solidified product. After crushing the dried solidified product in a mortar, XRD measurement was performed under the following conditions to obtain an X-ray diffraction pattern. The peak value P of the maximum intensity existing in the range of diffraction angle 2θ=27.000~29.980deg in the X-ray diffraction pattern was determined, and the peak line width Wa at 10% intensity of the maximum intensity and the peak line width Wb at 50% intensity of the maximum intensity were obtained. Then, the parameter X was calculated according to "X=Wa / Wb".

[0118] [XRD measurement conditions]

[0119] XRD apparatus: Sample horizontal type multi-purpose X-ray diffraction apparatus Ultima IV (manufactured by Rigaku Corporation)

[0120] X-ray source: CuKα rays

[0121] Scanning mode: 2θ / θ

[0122] X-ray tube voltage: 40kV

[0123] X-ray tube current: 40mA

[0124] Divergence slit: 1deg

[0125] Divergence longitudinal limiting slit: 10mm

[0126] Scattering slit: 1deg

[0127] Light receiving slit: 0.15mm

[0128] Kβ filter: None (using monochrome counter)

[0129] Scanning range: 3~90 degrees

[0130] Step: 0.01deg

[0131] Scanning speed: 0.5deg / min

[0132] <pH of slurry>

[0133] The pH (25° C.) of each of the slurries was measured using a PHL-40 manufactured by DKK-TOA CORPORATION.

[0134] <CMP Evaluation>

[0135] Using each of the above slurries, CMP evaluation was performed under the following conditions.

[0136] [CMP polishing conditions]

[0137] Polishing equipment: Reflexion LK CMP (manufactured by Applied Materials)

[0138] Slurry flow rate: 250mL / min

[0139] Substrate to be polished: A substrate to be polished having a 2 μm-thick silicon oxide film formed by plasma CVD on a silicon substrate was used as a blank wafer on which no pattern was formed.

[0140] Polishing pad: Foamed polyurethane resin with independent cells (manufactured by NITTA DuPont Incorporated, model IK4250H)

[0141] Grinding pressure: 27.6kPa (4psi)

[0142] Rotation speed of the polished substrate and polishing platform: polished substrate / polishing platform = 117 / 123rpm

[0143] Grinding time: 20 seconds and 50 seconds

[0144] Wafer cleaning: After the CMP process, the wafer is cleaned with water and ultrasonic waves, and then dried with a spin dryer.

[0145] The polishing speed of the silicon oxide film polished and cleaned under the above conditions was calculated by the following formula for 20 seconds of polishing and 50 seconds of polishing. The results are shown in Table 1. The film thickness difference of the silicon oxide film before and after polishing was calculated using an optical interference film thickness measuring device (manufactured by NOVA, product name: Nova i500).

[0146] Polishing speed = Difference in silicon oxide film thickness before and after polishing [nm] / Polishing time [min]

[0147] The polishing rate maintenance rate was calculated using the polishing rates of the 20-second polishing and the 50-second polishing according to the following formula.

[0148] Polishing speed maintenance rate [%] = (polishing speed for 50 seconds polishing [nm / min] / polishing speed for 20 seconds polishing [nm / min]) × 100 [Table 1]

[0149]

Claims

1. A slurry comprising abrasive grains and water, The abrasive grains include cerium oxide particles, In the X-ray diffraction pattern of the cerium oxide particles, in the peak with maximum intensity existing in the range of diffraction angle 2θ=27.000-29.980 degrees, the ratio Wa / Wb of the peak line width Wa at 10% of the maximum intensity and the peak line width Wb at 50% of the maximum intensity is 2.50-3.

30.

2. The slurry according to claim 1, wherein The ratio Wa / Wb is 2.70 to 3.

20.

3. The slurry according to claim 1, wherein The average particle size of the abrasive particles is 200 to 400 nm.

4. The slurry according to claim 1, wherein The content of the abrasive grains is 0.01 to 10.00 mass %. The slurry according to claim 1 , which has a pH of 1.00 to 7.

00. The slurry according to claim 1 , which is used for polishing a polishing surface containing silicon oxide. 7 . A polishing method comprising the step of polishing a surface to be polished using the slurry according to claim 1 .

Citation Information

Patent Citations

  • Polishing method

    JP1996022970A

  • Cerium oxide abrasive agent and polishing method of substrate

    JP1998106994A